Design of an arrangement of cubic magnets for a quasi-axisymmetric stellarator experiment. (1st December 2022) - Hammond, K.C.; Zhu, C.; Corrigan, K.; Gates, D.A.; Lown, R.; Mercurio, R.; Qian, T.M.; Zarnstorff, M.C.
Abstract: The usage of permanent magnets to shape the confining magnetic field of a stellarator has the potential to reduce or eliminate the need for non-planar coils. As a proof-of-concept for this idea, we have developed a procedure for designing an array of cubic permanent magnets that works in tandem with a set of toroidal-field (TF) coils to confine a stellarator plasma. All of the magnets in the design are constrained to have identical geometry and one of three polarization types in order to simplify fabrication while still producing sufficient field accuracy. We present some of the key steps leading to the design, including the geometric arrangement of the magnets around the device, the procedure for optimizing the polarizations according to the three allowable magnet types, and the choice of magnet types to be used. We apply these methods to design an array of rare-Earth permanent magnets that can be paired with a set of planar TF coils to confine a quasi-axisymmetric plasma with a toroidal magnetic field strength of about 0.5 T on axis.